Differences between skilled and less‐skilled young readers in the retrieval of semantic, phonological, and shape information. (1st February 2017) - Cortés‐Monter, Diana R.; Angulo‐Chavira, Armando Q.; Arias‐Trejo, Natalia
Abstract : This study aimed to determine whether the reading skills of third‐grade schoolchildren are associated with their preferences for semantic, phonological, and shape competitors (images or printed words) after being exposed to a spoken critical word. Two groups of children participated: skilled readers and less‐skilled readers. Through a language‐mediated visual search, children's fixations on the three competitors and a distractor were measured. When looking at images, both groups of readers preferred to look at the semantic competitor. When reading words, both groups showed a preference for the phonological competitor, but only skilled readers were sensitive to semantic information. These results suggest that early reading skills influence access to different types of representations in response to hearing a word, and they confirm the existence of a cascaded activation of information retrieval in childhood.